Following Health Measures in the Pandemic: A Matter of Values? - Schuster, Carolin (Frontiers in Psychology, 2021)
In three studies (N = 887), the hypothesis was tested that value consistency predicts intended Covid19 health behaviors and overrides other, utility-based motivational factors. Study 1 showed, accordingly, that intentions of social distancing was higher if it was perceived as more value-consistent. The higher value consistency, the less self-interest inconsistency and perceived efficacy of social distancing mattered for intentions. Study 2 failed to induce value consistency experimentally. However, correlative results show a similar moderation pattern as Study 1 regarding social distancing intentions, policy support, and devaluation of transgressors. In Study 3, higher value consistency of vaccination reduced the experimental effect of the vaccine’s prosocial efficacy but not the effect the vaccine’s self-interest efficacy. The findings are discussed regarding theoretical implications for the interplay of values and utility in motivation. In addition, implications for the potentially ambivalent effects of appealing to values to increase compliance are discussed.